Effectiveness of a Lesson and Laboratory Activity in Teaching Resistive Circuit Principles - Hood, Grant T.; Johnson, Donald M. (Journal of Agricultural Systems, Technology, and Management, 2021)
We evaluated the effectiveness of a lesson and laboratory activity for teaching the physical and electrical characteristics (Ohm’s law and Kirchhoff’s circuit laws) of series and parallel resistive circuits to students (n = 21) enrolled in a junior-level university agricultural electricity course in spring 2021. The lesson was delivered synchronously online during one 50- minute class period. The laboratory activity was conducted face-to-face during one 75- minute hands-on period following the lesson. Students completed a pre-test prior to the lesson, an immediate post-test after the lab activity, and a delayed post-test (as part of the unit exam) two weeks after the lab activity. The results of a repeated measures ANOVA indicated a statistically significant effect for the instructional treatment, F(2, 32) = 61.07, p < .001. Contrasts showed the means for both the immediate posttest [F(1, 16) = 89.53, p < .001] and the delayed posttest [F(1, 16) = 67.46, p < .001] were significantly higher than the mean on the pretest. These results indicated the lesson and laboratory instructional treatment was effective in increasing student knowledge of the physical and electrical characteristics of series and parallel resistive circuits. The η2 of 0.276 indicated a large effect for the instructional treatment on student learning.